Highly hydroxide-conducting hybrid anion exchange membrane with functional COF-enhanced ion nanochannels. (20th September 2021) - Chen, Jia; Li, Ping; Zhang, Ningxin; Tang, Shaokun
Abstract: Anion exchange membranes with potentially high conductivity and stability are urgently demanded in alkaline anion exchange membrane fuel cells (AEMFCs). However, the design and preparation of novel hydroxide-conducting material remain grand challenges. Herein, we demonstrate a significantly enhanced hydroxide conduction hybrid membrane with multi-ion nanochannels assembled by embedding two-dimensional covalent organic framework (COF) sheets into one-dimensional comb-shaped poly (2, 6-dimethyl-1, 4-phenylene oxide) (PPO) chains. Hydrophilic imidazole-based ionic liquids (im-IL) in-situ polymerize within the ordered pores of COF PI-2, forming long-range continuous ion channels. Then the poly ionic liquid-loaded covalent organic frameworks (im@PI-2) as a novel filler is embedded into imPPO to construct hybrid membranes with multi-ion nanochannels. A remarkable hydroxide conductivity of 147 mS/cm (80 °C and 100% RH) and a maximum power density of 140 mW/cm 2 are readily achieved for the hybrid membrane with 5 wt% im@PI-2 content. Particularly, the chemical stability, thermal stability, mechanical properties, and swelling resistance of the hybrid membrane are dramatically promoted by the introduction of im@PI-2. Meanwhile, the transfer of hydroxide in hybrid AEM is investigated by molecular dynamics simulations, which clarify the significant role of PI-2 one-dimensional channels in elevating hydroxide transport.